PENGARUH PERUBAHAN TATA GUNA LAHAN TERHADAP PENINGKATAN ALIRAN PERMUKAAN: STUDI KASUS DI DAS GATAK, SURAKARTA - Sudarto Sudarto; Muhammad Mukhlisin (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2010)
Floods and inundation have commonly occured in Surakarta city when rainfall intensity was high. This was due to the rapid change of land use. Based on this situation, this research was carried out for determining the influence of land use change in Gatak watershed. This watershed is located in the upper region of Surakarta city. The increasing surface runoff from Gatak area increases the flow discharge into Surakarta city. Results of this study showed that the land use of Gatak watersheds had rapidly changed from year 2001 to 2007. During this time period the land use change was about 9.95% from the total catchment area of 1152.97 hectares. The land use change had increased the surface runoff coefficient (C), from 0.286 in 2001 to 0.307 in 2007. Analysis of maximum discharge by using Rational Method and field observation showed the same trend. Similar rainfall intensity levels during 2001 and 2007 resulted in higher discharge flows in 2007 than those in 2001. If compared to the situation in early 2001, when flood did not occur, the increase of discharge has caused flood and inundation in these recent years.